Mind the task: Evidence on persistent gender gaps at the workplace - Marta Fana; Davide Villani; Martina Bisello (European Commission, Joint Research Centre (JRC), 2021)
This article investigates gender differences in tasks performed at the workplace over a period of 25 years, from 1991 and 2016 in France. We exploit data from the Enquête Complémentaire Emploi: Conditions de travail, the oldest survey at the worker level among European countries on a wide range of work attributes and working conditions measures. In our study, we focus both on the content of work form a material perspective, looking concretely at what job tasks are performed by men and women, and on work organisational practices, to capture gender disparities in authority and power relations at the workplace. Our findings reveal that women tend to perform different tasks compared to their male colleagues within the same job also after controlling for supply-side factors, like education, age and seniority. While in line with previous studies we find that women still tend to perform fewer physical tasks than men, despite significant increase in such activities in female dominated jobs, there is no strong evidence supporting the "brain" hypothesis. On the contrary, women appear to be less involved in intellectual tasks and, especially, social tasks such as managing and coordinating. Furthermore, social interactions with clients or customers do not significantly characterise feminised jobs, challenging the idea according to which gender segregation between jobs is explained by the predominance of this type of tasks. Additionally, and more importantly, our analysis shows that gender matters also in terms of work organisation and distribution of power, highlighting strong asymmetries in the way authority and autonomy are distributed between male and female workers, unbalanced in favor of men. Finally, our study shows that these gender effects often exacerbate within male dominated jobs, although they do not necessarily disappear as the share of female workers increases at the job level. We conclude that power and authority are structurally a prerogative of men, regardless of individual and job characteristics, even within female dominated jobs.
Keywords: 330; employment; working conditions; tasks; gender differences